Menu Variety, Macronutrient Intake, and Nutritional Status among Dormitory Students at Poltekkes Kemenkes Surabaya - Intan Ramadhan; Fahmi Hafid; Ani Intiyati; Dian Shofiya (Politeknik Kesehatan Kemenkes Surabaya, 2025)
This cross-sectional study aimed to analyze menu variations, macronutrient intake (energy, protein, fat, and carbohydrates), and nutritional status among students living in the Ministry of Health Polytechnic Dormitory, Surabaya. A total of 76 students were selected using proportional stratified random sampling. Data collection included a menu variation questionnaire, seven-day menu cycle observation, 2×24-hour food recall interviews, and anthropometric measurements (weight and height) to calculate Body Mass Index (BMI). Results showed that menu variation was classified as quite varied (55.3%). However, most respondents experienced deficits in energy (82.9%), fat (42.1%), and carbohydrates (98.7%), while normal protein intake was achieved by 52.6% of students. Dormitory meals contributed approximately 70% of daily energy needs, with the remaining 30% obtained from outside food purchases. Most students had a monthly allowance between IDR 500,000–IDR 1,000,000. Nutritional status assessment revealed that 56.6% were in the normal BMI category, 15.8% were underweight (wasting), and 17.1% were obese. Statistical analysis using Spearman Rank correlation indicated no significant relationship between menu variation and nutrient intake, or between nutrient intake and nutritional status (p > 0.05). These findings highlight the need for improved dormitory menu planning and nutrition education to enhance dietary adequacy and support students’ health.